PENTINGNYA PEMBELAJARAN MEMBACA, MENULIS, DAN BERHITUNG (CALISTUNG) PADA ANAK USIA DINI - Namira Putri Ramadhany (AZZAHRA, 2022)
Early childhood is a child with a golden age in development and growth to train their knowledge and motor skills. In the age range of 3-6, children are known as the golden age, which is a time when children experience stimulation and stimulation. The purpose of this study is to change the understanding of parents in accompanying their children while studying at home by providing activities on how to teach and learn to read, write and count (calistung) appropriate for early childhood. This activity itself is very necessary and important to do because it is a place for exchanging ideas and communicating between parents and educators. The research location is in Dasana Indah Housing, Tangerang Regency. The research uses a qualitative method with a case study and literature study approach. Data collection techniques through interviews, observations, and documentation/literature studies. The results showed that the importance of the role of parents in learning calistung in early childhood. So that early childhood is able to prepare to enter a higher level of education.